2021
DOI: 10.3390/agronomy11071363
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Estimation of Crop Biophysical Parameters Using Multi-Source and Multi-Temporal Remote Sensing Observations

Abstract: Remote sensing data are considered as one of the primary data sources for precise agriculture. Several studies have demonstrated the excellent capability of radar and optical imagery for crop mapping and biophysical parameter estimation. This paper aims at modeling the crop biophysical parameters, e.g., Leaf Area Index (LAI) and biomass, using a combination of radar and optical Earth observations. We extracted several radar features from polarimetric Synthetic Aperture Radar (SAR) data and Vegetation Indices (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…Gradient Boosted Regression Trees (GBRT) takes advantage of boosting as a statistical approach to aggregate weak learners and convert them to a single strong learner model. This model minimizes the residuals, diminishes the loss function, and optimizes the prediction by generating new decision trees and adding them in sequential steps (Bahrami et al 2021). Furthermore, the GBRT algorithm is sensitive to its parameters; hence, appropriate parameter selection, including the number of estimators, maximum depth, learning rate, loss function, and so forth assists in reaching the best algorithm implementation and final result.…”
Section: Gradient Boosted Regression Treesmentioning
confidence: 99%
“…Gradient Boosted Regression Trees (GBRT) takes advantage of boosting as a statistical approach to aggregate weak learners and convert them to a single strong learner model. This model minimizes the residuals, diminishes the loss function, and optimizes the prediction by generating new decision trees and adding them in sequential steps (Bahrami et al 2021). Furthermore, the GBRT algorithm is sensitive to its parameters; hence, appropriate parameter selection, including the number of estimators, maximum depth, learning rate, loss function, and so forth assists in reaching the best algorithm implementation and final result.…”
Section: Gradient Boosted Regression Treesmentioning
confidence: 99%
“…Some researchers have tried to improve the prediction ability of the models of LAI by fusing LiDAR data with spectral data [83]. In addition, Bahrami et al [84] constructed prediction models of LAI and biomass by combining Li-DAR and optical earth observations. Luo et al [85] estimated the biomass of short, wetland reed using a combination of LiDAR and hyperspectral data, and found that combining the LiDAR with hyperspectral data could improve the estimation accuracy of reed biomass.…”
Section: Models Of Lai Constructed With Multimodal Datamentioning
confidence: 99%
“…In this regard, several machine learning regression algorithms (MLRAs) have been utilized to retrieve bio and geophysical parameters from both optical [32][33][34][35][36][37] and SAR [38][39][40][41] data. In particular, machine learning algorithms attempt to find a linear or a non-linear relationship among the features (e.g., linear polarizations) and the target (e.g., PAI, WB, etc.).…”
Section: Introductionmentioning
confidence: 99%